DIGTIAL TECHNOLOGIES IN COMBATING GLOBAL CORRUPTION - Vinnykova, Nataliya (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2022)
A transnationalization of corruption practices, born by globalization processes, is one of nowadays negative phenomenon that deserves intensive studying. Digital technologies smooth the pathways for transnational corruption. On the other hand, digitalization also provides tools for building up respective countermeasures. This article examines the potential of digital technologies, primarily artificial intelligence (AI), in preventing corruption practices. Firstly, the characteristics of the «global corruption» phenomenon are outlined. The experience of implementing digital technologies in the corruption countermeasures has been analysed that revealed problems and prospective trends in the development of digital anti-corruption mechanisms at the supra-national level of governance. Digital tools for detecting and tracking of transnational corruption schemes were described in the framework of international journalistic investigations or anti-corruption control technologies in the European Union. One of key factors preventing the effective application of AI against the transnational corruption is the lack of the consolidated international regulatory regime for data evaluation. However, AI is ambivalent for both fighting corruption and creation new corruption pathways. Arguments in support of the distributed ledger technologies as the promising corruption-preventing techniques are provided. The study discloses factors inhibiting the scaling of the implementation of blockchain or smart contracts as mechanisms of reducing the risks of corruption. The need to develop international standards for the use of AI technologies in the fight against corruption practices is emphasized. The creation of a transnational structure with appropriate rule-making and control powers in this area becomes extremely important.